2007
DOI: 10.1523/jneurosci.3948-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

P2Y1Receptor Modulation of the Pre-Bötzinger Complex Inspiratory Rhythm Generating NetworkIn Vitro

Abstract: ATP is released during hypoxia from the ventrolateral medulla (VLM) and activates purinergic P2 receptors (P2Rs) at unknown loci to offset the secondary hypoxic depression of breathing. In this study, we used rhythmically active medullary slices from neonatal rat to map, in relation to anatomical and molecular markers of the pre-Bötzinger complex (preBötC) (a proposed site of rhythm generation), the effects of ATP on respiratory rhythm and identify the P2R subtypes responsible for these actions. Unilateral mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
154
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(168 citation statements)
references
References 79 publications
(138 reference statements)
10
154
2
2
Order By: Relevance
“…In addition, the following antagonists of fast excitatory and inhibitory transmission were used: 100 M D-(Ϫ)-2-amino-5-phosphonopentanoic acid (D-AP5; an NMDA receptor antagonist; Tocris Bioscience), 20 -100 M 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX; a nonNMDA receptor antagonist; Tocris Bioscience), 10 M bicuculline methiodide (a GABA A receptor antagonist; Sigma-Aldrich), and 10 M strychnine (a glycine receptor antagonist; Tocris Bioscience). The drug concentrations and the application time were similar to those used in previous studies (Bongianni et al, 1999(Bongianni et al, , 2002(Bongianni et al, , 2006Aberger et al, 2001;Le Ray et al, 2003Shao and Feldman, 2002;Tryba et al, 2003;Peña et al, 2004;Del Negro et al, 2005;Lorier et al, 2007;Shao et al, 2008;St. John and Leiter, 2008;Mutolo et al, 2010).…”
Section: Methodssupporting
confidence: 78%
“…In addition, the following antagonists of fast excitatory and inhibitory transmission were used: 100 M D-(Ϫ)-2-amino-5-phosphonopentanoic acid (D-AP5; an NMDA receptor antagonist; Tocris Bioscience), 20 -100 M 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX; a nonNMDA receptor antagonist; Tocris Bioscience), 10 M bicuculline methiodide (a GABA A receptor antagonist; Sigma-Aldrich), and 10 M strychnine (a glycine receptor antagonist; Tocris Bioscience). The drug concentrations and the application time were similar to those used in previous studies (Bongianni et al, 1999(Bongianni et al, , 2002(Bongianni et al, , 2006Aberger et al, 2001;Le Ray et al, 2003Shao and Feldman, 2002;Tryba et al, 2003;Peña et al, 2004;Del Negro et al, 2005;Lorier et al, 2007;Shao et al, 2008;St. John and Leiter, 2008;Mutolo et al, 2010).…”
Section: Methodssupporting
confidence: 78%
“…It was shown previously that P2Y1 receptors mediate the excitatory effects of ATP on neurons in the preBötzinger complex (Lorier et al 2007(Lorier et al , 2008. However, we found that P2Y1 receptors are not expressed by chemosensitive RTN neurons and do not contribute to CO 2 /H + sensitivity of these cells in vitro or to CO 2 -induced changes in breathing or blood pressure in vivo.…”
Section: Contribution Of Purinergic Signalling To Rtn Chemoreceptioncontrasting
confidence: 61%
“…Não podemos descartar a participação de outros receptores P2Y, pois resultados recentes mostraram que os receptores P2Y são os receptores purinérgicos mais abundantes na região do Complexo de Pré-Botzinger e medeiam as respostas respiratórias produzidas pelo ATP (FUNK, 2013;LORIER et al, 2007LORIER et al, , 2008.…”
Section: Contribuição Da Sinalização Purinérgica Na Região Do Rtn No unclassified
See 2 more Smart Citations